Case Report: A rare small bowel sarcoma - Guo, Jiwu; Mao, Jie (Frontiers in Surgery, 2025)
Intestinal sarcomas are rare gastrointestinal tumors but their etiology is not clear. A middle-aged man was admitted to hospital on 11 April 2023 because of intermittent melena for 1 month. Gastroscopy and colonoscopy were inconclusive, however, melena persisted. Abdominal magnetic resonance imaging indicated a left mid-abdominal mass and lymphoma of the small bowel origin. Small bowel enteroscopy revealed infiltrating periannular ulcer lesions in the jejunum. He underwent an operation and a partial resection of the small intestine was performed. The pathological examination revealed mesenchymal, highly malignant, poorly differentiated sarcoma. The patient died 6 months after surgery. The patient had been diagnosed with hepatocellular cancer and received immune checkpoint inhibitors (PD-1, sintilimab) combined with bevacizumab for 14 cycles 19 months before being diagnosed with intestinal sarcoma, and achieved complete remission. While immunotherapy achieves good therapeutic effects, another problem that has to be paid attention to is immune-related adverse reactions, which involve multiple systems. Based on the above information, we believe that this small bowel sarcoma was a rare complication of immunotherapy.